TRPC3, an underestimated, universal pacemaker channel?. (December 2021) - Tiapko, Oleksandra; Groschner, Klaus
Highlights: TRPC3 is a background "leak channel" in midbrain dopamine neurons. TRPC3 constitutive activity provides inward currents during slow depolarization to promote pacemaker firing of dopaminergic neurons. TRPC3 emerges as a versatile component of the neuronal pacemaking- and spike frequency-modulation toolbox. Abstract: Transient receptor potential channel canonical 3 (TRPC3) is a cation channel with poor Ca 2+ selectivity and significant constitutive activity. One of the channels' features is its striking ability to couple in a surprisingly versatile manner to different down-stream signaling pathways, thereby serving cellular functions in a tissue specific manner. Expression of this protein is prominent in excitable cells, and its activity has repeatedly been implicated in electrical pacemaking. Previous studies demonstrated a linkage between constitutive activity of TRPC3 and neuronal firing in hippocampus and cerebellum. A most recent report from the Park laboratory corroborates the concept of TRPC3 functioning as a critical element in the neuronal pacemaking machinery for dopaminergic neurons of substantia nigra. Conclusively, mechanistic coupling between TRPC3 activity and firing frequency appears evident for different types of neurons, highlighting the potential of TRPC3 as a universal as well as multifunctional pacemaker channel. Graphical abstract: Image, graphical abstract